Designing Albaha Internet of Farming Architecture - A Alahmadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Up to now, most farmers in Albaha, Saudi Arabia are still practicing traditional way, which is not optimized in term of water usage, quality of product, etc. At the same time, nowadays ICT becomes a key driver for Innovation in Farming. In this project, we propose a smart Internet of farming system to assist farmers in Albaha to optimize their farm productivity by providing accurate information to the farmers the right time prediction to harvest, to fertilize, to watering and other activities related to the farming/agriculture technology. The proposed system utilizes wireless sensor cloud to capture remotely important data such as temperature, humidity, soil condition (moisture, water level), etc., and then they are sent to a storage servers at Albaha University cloud. An adaptive knowledge engine will process the captured data into knowledge and the farmers can retrieve the knowledge using their smartphones via the Internet.